PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN RISIKO TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perbankan yang Terdaftar di Bursa Efek Indonesia 2017-2018) - Kusumastuti, Isna Neysa; Ghozali, Imam (Diponegoro Journal of Accounting, 2020)
The aim of this study is to examine the effect of Good Corporate Governance mechanism and risk disclosure on company performance. The dependent variable in this study is the financial performance of an accounting-based company as measured by return on assets, while the independent variables in this study are the number of board meetings, the financial expertise of the audit committee, the size of public accounting firm, the size of the risk monitoring committee, and the level of risk disclosure.The populations in this study consists of banking sector financial companies on the Indonesian Stock Exchange for the period 2017-2018. Sample determined with purposive sampling method. The total sample of this research is 74 companies.This study uses multiple regression analysis with SPSS software for hypothesis testing. The results of this study indicate that the audit committee's financial expertise and level of risk disclosure have a positive effect on the company's financial performance. While the number of board of commissioners meetings, the size of public accounting firm, and the size of the risk committee as measured by the number of risk monitoring committee meetings does not affect the company's financial performance.